2003
DOI: 10.1093/brain/awg142
|View full text |Cite
|
Sign up to set email alerts
|

Parkin disease: a phenotypic study of a large case series

Abstract: Mutations in the parkin gene, PARK2, are a common cause of parkinsonism in familial as well as isolated cases with an age of onset <40 years and should be considered in the diagnostic work up of young-onset parkinsonism. We report a detailed clinical evaluation of a personal series of 24 patients with mutations in the parkin gene. The clinical presentation of most cases was broadly comparable to that of previous descriptions of autosomal recessive early-onset or juvenile parkinsonism and young-onset Parkinson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
262
6
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(285 citation statements)
references
References 35 publications
14
262
6
3
Order By: Relevance
“…While many patients have family history of PD, as seen in our study, sporadic cases have been also reported developing at the age of 40 years [12][13][14] . Their clinical presentation can be similar to idiopathic PD but they remarkably have dystonia in lower limbs, which was not seen in our group.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…While many patients have family history of PD, as seen in our study, sporadic cases have been also reported developing at the age of 40 years [12][13][14] . Their clinical presentation can be similar to idiopathic PD but they remarkably have dystonia in lower limbs, which was not seen in our group.…”
Section: Discussionsupporting
confidence: 60%
“…The gene locus for this form of parkinsonism was mapped in 6q25.2-27 chromosome 12 . PARK2 patients develop EOPD around the age of 20-30 and show distinct clinical characteristics compared to idiopathic PD (slow progress, dystonia at onset involving lower limbs, and dyskinesia after low-dose L-DOPA) 13 . Interestingly, pathologically, these patients do not have Lewy bodies 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another gene down-regulated by N-myc with a similar expression profile to parkin, NDRG1 (N-myc down-regulated gene 1), is involved in growth arrest and cell differentiation and is mutated in hereditary motor and sensory neuropathy-Lom (27). The involvement of autosomal-recessive loss of function mutations in NDRG1 in human peripheral neuropathy may be all the more relevant to parkin-linked disease, in that loss-offunction parkin mutations have also been identified in human patients with peripheral and sensory neuropathy (28,29). It is conceivable that the mechanisms of neurodegeneration resulting from mutations in the parkin or NDRG1 gene overlap, at least in the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The age-related and progressive signs of PD classically include resting tremor, muscular rigidity, abnormal gait, and slow movement; however, other signs and symptoms associated with parkinsonism can include somatosensory deficits, impaired cognitive function, and psychiatric disturbances (2)(3)(4). Many PD signs result from the degeneration of dopaminergic neurons in the substantia nigra pars compacta.…”
mentioning
confidence: 99%